Increasing cryospheric hazards in a warming climate - Ding, Yongjian; Mu, Cuicui; Wu, Tonghua; Hu, Guojie; Zou, Defu; Wang, Dong; Li, Wangping; Wu, Xiaodong (Earth-science reviews, 2021)
The cryosphere is an important component of the global climate system. Cryospheric components are sensitive to climate warming, and changes in the cryosphere can lead to serious hazards to human society, while the comprehensive understanding of cryospheric hazards largely remains unknown. Here we summarized the hazards related to atmospheric, oceanic and land cryosphere. The different types of cryospheric hazards, including their phenomena, mechanisms and impacts were reviewed. Our results suggested that: 1) The recorded hazards from atmospheric cryosphere including frost, hail, freezing rain decreased or showed great spatial heterogeneities, while their future changes are difficult to predict, and the extreme cold events in winter may increase in the future; 2) Sea ice extent declines rapidly, and iceberg numbers will increase. The permafrost-dominated coastline erosion will be exacerbated by climate warming. Meanwhile, the sea level rise is expected to continue in the next decades; 3) The glacier collapse, glacial lake outbursts and paraglacial readjustments will increase in the future. Although the total area of snow cover will decrease, the heavy snow events, snow avalanches, and snowmelt floods will not decrease simultaneously. The permafrost-related rock and debris flow and thaw slump will also increase with permafrost degradation. Taken together, we concluded the cryosphere is shrinking, while cryospheric hazards will likely increase in a warming climate. [Display omitted] •The cryosphere components have been shrinking due to climate warming.•Hazards from atmospheric cryosphere decreased, while future changes are unknown.•Sea ice extent and icebergs are declining, but their risks remain unchanged.•The hazards from glacier, permafrost will increase in the future.•Prediction, monitoring and warning of cryospheric hazards are important.